Transient accumulation of Mg-protoporphyrin IX regulates expression of PhANGs - New evidence for the signaling role of tetrapyrroles in mature Arabidopsis plants - Zhang, Zhong-Wei (Journal of plant physiology, 2011)
Copyright © 2010 Elsevier GmbH. All rights reserved.